P42 The standard deviation: challenges of implementing a standards framework ASPIH. (5th November 2017) - Cocking, Caroline; Baker, J
Abstract : Background: The Resuscitation and Clinical Skills Department at the Royal Derby Hospital has a dedicated simulation facility. The team comprises 16 resuscitation/clinical skills trainers with technician/admin support delivering mandatory resuscitation training, accredited courses and medical education. All education delivered incorporates an element of simulation from part-task trainer to high fidelity manikins. The profile of patient safety continues to increase demand for simulation within the trust and the wider healthcare community, presenting a challenge for the team, with potential to cause deviance of implementation of the ASPiH standards. The initial consultation process revealed that substantial work was required to enable progression to accreditation. Project Description: This presentation/poster will give a practical example of how systems and non-technical factors impact on the quality of the adoption of ASPiH standards and accreditation. Outcomes: A review of the standards confirmed that we have some excellent and robust systems in place which respond to changing requirements and perceived gaps in educational need. Gaps and discrepancies in the structure of the resources within the department are evident. Faculty training is varied with limited evidence and records; competency in the art of de- briefing is rarely formally reviewed. Faculty training days are provided by an external educator and attendance is recorded, however support and review post-course is unstructured and not documented. The department technician has core responsibilities and works collaboratively with the undergraduate/post-graduate teams. Simulation is not identified in the job role. The patient perspective is not considered in the written simulations, paperwork is not kept up to-date for the scenarios and there is minimal simulated patient use. There is a culture of ' it will do' or 'it's near enough' when setting up/planning simulations, attention to detail is poor at times i.e., Equipment does not always mirror clinical practice. Recommendations: To ensure adoption of the standards there is a requirement to embed this within the culture of the team. A clear structure and process is required to ensure understanding of the framework as a tool to improve and sustain the quality of our simulation practice. Work has commenced on addressing the identified gaps; All faculty can evidence relevant facilitation skills within SBE; opportunity for expansion of the technician role to include simulation; written simulations to be reviewed and updated annually to reflect clinical documentation and guidelines; equipment to mirror the clinical environment, links established with key personnel within the trust.